2018
DOI: 10.1007/s12038-017-9728-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant reference genes for development and stress response studies

Abstract: Many reference genes are used by different laboratories for gene expression analyses to indicate the relative amount of input RNA/DNA in the experiment. These reference genes are supposed to show least variation among the treatments and with the control sets in a given experiment. However, expression of reference genes varies significantly from one set of experiment to the other. Thus, selection of reference genes depends on the experimental conditions. Sometimes the average expression of two or three referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 99 publications
1
109
0
Order By: Relevance
“…Similar to geNorm, NormFinder indicated that ADP was the least stable gene in all treatments. Although there were some differences in Forests 2020, 11,193 9 of 17 rankings between geNorm and NormFinder, the top five most stable genes were relatively consistent between them. NormFinder analysis: the NormFinder approach provides a stability value for each gene based on inter-and intra-group variation in expression [15].…”
Section: Gene Stability Gene Stability Gene Stability Gene Stability mentioning
confidence: 98%
See 3 more Smart Citations
“…Similar to geNorm, NormFinder indicated that ADP was the least stable gene in all treatments. Although there were some differences in Forests 2020, 11,193 9 of 17 rankings between geNorm and NormFinder, the top five most stable genes were relatively consistent between them. NormFinder analysis: the NormFinder approach provides a stability value for each gene based on inter-and intra-group variation in expression [15].…”
Section: Gene Stability Gene Stability Gene Stability Gene Stability mentioning
confidence: 98%
“…Forests 2020, 11,193 7 of 18 heat stress. The ranking of gene stability by average CV values across all treatments was PP2A (Table 2).…”
Section: Expression Profiles Of Candidate Rgsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 2 and Table 2, all 14 RGs showed average M values less than 1.5 under drought, high salinity, cold stress, and ABA treatment. Sometimes a single RG does not meet the stability requirements for use in normalization, and two or more RGs are therefore needed to reduce error and obtain more accurate results [28]. geNorm can determine the optimal number of candidate RGs based on the calculation of pairwise variation (Vn/Vn+1).…”
Section: Genorm Analysismentioning
confidence: 99%